Hermeneutics Controvercies in Contemporary Islamic Studies - Nurkhalis, Nurkhalis; Fauzan, Fauzan (KALAM, 2023)
Hermeneutics has changed the paradigm of the study of contemporary Islamic thought towards the direction of Islamic science, placing modern Islamic issues into the discourse of theodiplomacy. Many modernist scholars have initiated an overhaul of the concept of "soar skyward" Islam, offering through hermeneutics a "down-to-earth" idea of Islam. Hermeneutics has given birth to various controversies through the use of the methods "to explain," "to interpret," and "to say," ignoring the approaches of al-shadaf (charismatic study), al-lubab (essence study), tahqiq (ensuring the exploration of the position of words), and tadqiq (comparing to the opinions of competent scholars). This study was conducted using qualitative research with a descriptive approach. The results showed that hermeneutics has initiated the occurrence of rereading, reinterpretation, rethinking, renewing, and rebuilding to strive for adjustments toward the new Islamic order. Therefore, the existence of Hermeneutics does not make calculations of right and wrong, strong and weak, black and white, and Islam-West in every interpretation of the Qur'an. It's just that the interpretation of modernity issues carried out by the approach of Islamization of science and applied Islamology giving birth to various worldview controversies such as Progressive Islam, pluralist Islam, humanist Islam, and reverse Islam.